An insight into postharvest pericarp browning in litchi (Litchi chinensis Sonn.) - Mir, Hidayatullah; Homa, Fozia; Perveen, Nusrat (Journal of Postharvest Technology, 2015)
Litchi (Litchi chinensis Sonn.), one of the most important fruits of tropical and subtropical world is highly prized for its perfectly blended sweet-acidic juicy pulp. The attractive bright red or pink colour of litchi pericarp which determines the consumer acceptance is attributed to the presence of a class of flavonoids, anthocyanin which is lost and turns brown within 2- 3 days of harvesting if stored under ambient conditions. Post-harvest browning is an important factor limiting the quality and storage life of litchi fruits and has been attributed mainly to degradation of anthocyanins, along with the oxidation of phenolic compounds present in the pericarp by enzymes like polyphenol oxidase (PPO) and/or peroxidase (POD). Since, PPO, which is the main enzyme involved in browning has a low affinity to litchi pericarp anthocyanin, it is supposed that the anthocyanins are first hydrolysed by anthocyanase, resulting in formation of anthocyanidin which in turn is oxidized by PPO and/or POD resulting in oxidative browning. The current research endeavors focuses on prolonging the shelf life of litchi fruits using different post-harvest treatments which can maintain the pericarp membrane integrity thus, avoiding loss of compartmentalization between litchi pericarp oxidase enzymes and their substrates and in turn preventing browning.